Cluster of differentiation 36 gene polymorphism (rs1761667) is associated with dietary MUFA intake and hypertension in a Japanese population. Issue 11 (28th May 2019) - Fujii, Ryosuke; Hishida, Asahi; Suzuki, Koji; Imaeda, Nahomi; Goto, Chiho; Hamajima, Nobuyuki; Wakai, Kenji; Kondo, Takaaki
Abstract: Cluster of differentiation 36 ( CD36 ) is a membrane receptor expressed on a wide variety of human cells. CD36 polymorphisms are reportedly associated with oral fat perception, dietary intake and metabolic disorders. The present study examined associations of two CD36 polymorphisms (rs1761667 and rs1527483) and dietary fat intake, and metabolic phenotypes in a Japanese population. This cross-sectional study was conducted based on clinical information collected from health check-ups in Japan ( n 495). Dietary nutrient intake was estimated from a validated short FFQ and adjusted for total energy intake using the residual method. Mean blood pressure was calculated from systolic blood pressure (SBP) and diastolic blood pressure (DBP). Hypertension was defined as SBP ≥ 130 mmHg and/or DBP ≥ 85 mmHg, or use of antihypertensive drugs. Genotyping was performed using PCR with confronting two-pair primers method. Mean age was 63·4 (sd 9·9) years. Individuals with the AA genotype showed higher total fat and MUFA intake (standardised β = 0·110 and 0·087, P = 0·01 and 0·05, respectively) compared with the GG and GA genotypes. For metabolic phenotypes, the AA genotype of rs1761667 had a lower blood pressure compared with the GG genotype (standardised β = –0·123, P = 0·02). Our results suggested that the AA genotype of rs1761667 in the CD36 gene was associated with higher intake of total fat and MUFA and lower risk of hypertension in a Japanese population.